2005
DOI: 10.1007/s00425-004-1449-5
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of abscisic acid in the induction of secondary somatic embryogenesis on seed-coat-derived carrot somatic embryos

Abstract: When seed coats (pericarps) were picked from 14-day-old carrot (Daucus carota) seedlings and cultured on agar plates, embryogenic cell clusters were produced very rapidly at a high frequency on the open side edge. Embryo induction progressed without auxin treatment; indeed treatment caused the formation of non-embryogenic callus. The embryogenic tissues (primary embryos) developed normally until the torpedo stage; however, after this a number of secondary somatic embryos were produced in the hypocotyl and root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
17
1
1
Order By: Relevance
“…In current study secondary embryos were identified in maturation medium. Some studies have correlated the formation of secondary somatic embryos depending on the concentration of exogenous ABA (Iida et al 1992, Ogata et al 2005, Aman and Afrasiab 2014 or the types of somatic embryos placed in MM with ABA (Lee et al 1998, Calic et al 2012.…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%
“…In current study secondary embryos were identified in maturation medium. Some studies have correlated the formation of secondary somatic embryos depending on the concentration of exogenous ABA (Iida et al 1992, Ogata et al 2005, Aman and Afrasiab 2014 or the types of somatic embryos placed in MM with ABA (Lee et al 1998, Calic et al 2012.…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%
“…9,11,13 and in dicots (Daucus carota, Hevea). 8,10,12 Our experiment in chicory established that 50 mM ABA promoted the ISE whereas 100 mM had a slightly negative effect. Thus, our results are in agreement with results already described in the literature.…”
Section: Discussionmentioning
confidence: 72%
“…[5][6][7] In various models of SE, the exogenous supply of abscisic acid (ABA), a well-known stress hormone of plants, also led to increase the ISE. [8][9][10][11][12] Also, the report of an extracellular matrix connecting cell wall-plasmalemma-cytoskeleton led to the hypothesis that the cell wall could be sensitive to osmotic stresses. [13][14][15][16] Supporting this possibility, several groups reported that treatments with plasmolysing agents led to increase the ISE of gymnosperms and Eleutherococcus.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective method seems to be somatic embryogenesis (SE) (Gude and Dijkema 1997), which enables large-scale propagation of many geophytes (Stefaniak 1994; Nhut et al 2006;Bakhshaie et al 2010;Gao et al 2010;Subotić et al 2010). Somatic embryogenesis also makes it possible to investigate factors involved in the process (Find 1997;Senger et al 2001) and to study the physiological, biological, and molecular events occurring during embryo development (Zimmerman 1993;Ogata et al 2005;Quiroz-Figueroa et al 2006). To induce somatic organogenesis, the culture medium is supplemented mainly with an auxin, which determines the initiation of somatic embryos (Zimmerman 1993;Dodeman et al 1997;Gude and Dijkema 1997;Raghavan 1997, Bach andPtak 2001).…”
Section: Introductionmentioning
confidence: 99%
“…BAP (Malik 2008;Maślanka and Bach 2010). Initiated somatic embryos can develop into whole plants under appropriate conditions (Ogata et al 2005). For proper maturation and conversion, somatic embryos must first achieve morphological maturity and then-by undergoing a desiccation period-physiological maturity (Stasolla and Yeung 2003).…”
Section: Introductionmentioning
confidence: 99%